Femininity in the Position of the Oppressed in Nino Ricci’s Lives of the Saints A Comparison to Nelly Arcan’s Putain in Canadian and Quebec Literary Portrayals of Contemporary Womanhood - Drab, Ewa (Romanica Silesiana)
Nino Ricci, an award-winning English-speaking Italian descendant, and Nelly Arcan, suicidal Quebecker from Montreal, portray contemporary womanhood as seen through the lenses of oppression. In Ricci’s Lives of the Saints the figure of mother becomes a curse of the woman’s son, whose whole existence is conditioned by his mother’s incidental and adulterous pregnancy. The mother shifts from the position of an individual to the position of a symbol by becoming sinful representation of her disobedience in the relation to social rules. She is dominated by masculine gaze and rules established by men. Inversely acts Cynthia, the prostitute in Nelly Arcan’s Putain, who chooses her fate intentionally but who is equally conditioned by the social environment in which she grew up. Being a prostitute is an act of succumbing to masculine tyranny. Key words: womanhood, oppressor, subjugation, Ricci, Arcan.